Flow through ring resonator sensing platform. Issue 86 (18th September 2015) - Grimaldi, I. A.; Testa, G.; Bernini, R.
<x xml:space="preserve">Abstract</x> Polymeric microring resonator platform employing a flow-through approach is realized. A reduction of more than one order of magnitude of the sensor response time respect to standard flow-over approach is obtained.